GAMBARAN KEPATUHAN KONSUMSI TABLET TAMBAH DARAH PADA REMAJA PUTRI - Nurul Budiana; supardi; Wiwin Rohmawati; Endang Sawitri (MOTORIK Jurnal Ilmu Kesehatan, 2025)
Adolescence is a period of transition toward adulthood. One of the key public health concerns for the government is the prevention of anemia in adolescent girls. Iron deficiency anemia is a global issue. The prevention and management of anemia in adolescent girls are carried out through the administration of one iron supplement tablet per week, making adherence to iron tablet consumption crucial in reducing iron deficiency rates. This study aims to describe the adherence of adolescents in consuming iron supplement tablets in Dukuh Village. Method: This research is a quantitative study. The population consisted of 261 respondents, with a sample of 73 adolescent girls selected using a purposive sampling technique. The study was conducted in Dukuh Village, Bayat, Klaten, from July 1, 2024, to July 30, 2024. Results: The most common age group among the respondents was early adolescence (ages 12–15), with 33 respondents (45.2%), while the least common age group was late adolescence (ages 19–21), with 10 respondents (13.7%). The majority of respondents had a high school education (41.1%), while the least had only an elementary school education (6.8%). Most respondents were categorized as non-adherent, with 43 respondents (58.9%) failing to comply with iron tablet consumption.Conclusion: The findings of this study in Dukuh Village indicate that the majority of adolescent girls fall into the non-adherent category, with 43 respondents (58.9%) not complying with iron tablet consumption